Linguistic ethnography : interdisciplinary explorations - Snell, Julia, 1979-; Shaw, Sara, 1969-; Copland, Fiona, 1962- (Houndmills, Basingstoke : Palgrave Macmillan, 2015)
The collection demonstrates the ways in which established traditions and scholars have come together under the umbrella of linguistic ethnography to explore important questions about how language and communication are used in a range of settings and contexts, and with what effect.
1 An Introduction to linguistic ethnography: interdisciplinary explorations -- 2 Theory and method in linguistic ethnography -- 3 Workplace literacies and audit society -- 4 Between text and social practice: balancing linguistics and ethnography in journalism studies -- 5 How linguistic ethnography may enhance our understanding of electronic patient records in health care settings -- 6 Examining talk in post-observation feedback conferences: learning to do linguistic ethnography -- 7 Researching health policy and planning: the influence of linguistic ethnography -- 8 Bursting the bonds: policing linguistic ethnography -- 9 The Geography of communication and the expression of patient's concerns -- 10 Applying linguistic ethnography to educational practice: notes on the interaction of academic research and professional sensibilities -- 11 Partnership in research: doing linguistic ethnography with and for practitioners -- 12 Linguistic ethnography perspectives on working-class children's speech: challenging discourses of deficit -- 13 Hip hop, education and polycentricity -- 14 Metacommentary in linguistic ethnography
Elektronická reprodukce.
Keywords: etnolingvistika; ethnolinguistics; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online